HUBUNGAN ANTARA KECERDASAN EMOSI DENGAN KONTROL DIRI PESERTA DIDIK DI KELAS VII SMP MUHAMMADIYAH 6 PADANG - Ariesta, Firdila - (Bimbingan dan Konseling, 2014)
Background of this research was difference level of emotional intelligence individual thatdistinguish how to way individual self control. This research aimed to (1) describe emotionalintelligence of students, (2) describe self control of students, (3) the correlate between emotionalintelligence by self control of students. Kind of this research is quantitative correlationaldescriptive. The population in research is all of students in class VII SMP Muhammadiyah 6Padang academic year 2013/2014 that amounted 206 people, and research sample taken by using aproportional random sampling technique that amounted 73 people. The research instrument was aquestionnaire, for data analysis using percentage techniques and correlation techniques. The resultsof data analysis: (1) describe emotional intelligence of students into in the category intelligencewith the percentage 34,24% , (2) description of self control into in the category enough good withthe percentage 38,36%, (3) the correlation of emotional intelligence by self control of studentsobtained count of r 0,530 and r table 0,235 df 71 at the significance level of 0,05 with a 95%,meaning the count r more that r table (0,530> 0,235). The results of research obtained relationemotional intelligence by self control of students in class VII SMP Muhammadiyah 6 Padang atthe significance enough accurate. Things what to do to improve emotion intelligence and selfcontrol from teacher participate can attention of emotional aspects, the emotion development andself control of students as well. The researchers recommend continued research to researchingabout emotional intelligence in terms of other aspects.